Long Rang Trans-Boundary Air Pollution Smelter Case Arbitration Outcome - Negesse Asnake AYALEW (Indonesia Strategic Sustainability, 2020)
The purpose of the investment is to bring benefits to the owners and sustainable development for the local community and for future generations. Arbitration is the process of resolving legal disputes between individuals, groups and countries. Every investment activity must ensure sustainable development to respect the rights of future generations. However; Canadian zinc smelting companies emit sulfur dioxide and cause air pollution in the United States. This created a dispute between Canada and the United States, then they agreed to settle it through a neutral arbitration court. As a result, this arbitration court ruling creates two principles of international environmental law primarily; the polluter pays the principle and obligation of the state not to damage the environment outside its jurisdiction. This arbitration award establishes the concept of Harm across borders and the principle of polluter pays to ensure the sovereignty of international environmental law. Therefore; if disputes arise between countries, they can resolve them through peaceful dispute resolution mechanisms such as negotiation, mediation and arbitration